2014
DOI: 10.3389/fendo.2014.00170
|View full text |Cite
|
Sign up to set email alerts
|

Functions of Two Distinct “Prolactin-Releasing Peptides” Evolved from a Common Ancestral Gene

Abstract: Prolactin-releasing peptide (PrRP) is one of the RF-amide peptides and was originally identified in the bovine hypothalamus as a stimulator of prolactin (PRL) release. Independently, another RF-amide peptide was found in Japanese crucian carp and named Carassius-RFa (C-RFa), which shows high homology to PrRP and stimulates PRL secretion in teleost fish. Therefore, C-RFa has been recognized as fish PrRP. However, recent work has revealed that PrRP and C-RFa in non-mammalian vertebrates are encoded by separate g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 119 publications
(279 reference statements)
0
14
0
1
Order By: Relevance
“…Wang et al (2012) identified new chicken PrRP and showed that there are two types of PrRP encoded by separate genes. They also demonstrated that the chicken PrRP we previously identified (Tachibana et al, 2011; Tachibana and Sakamoto, 2014) is an ortholog of C-RFa, and newly identified chicken PrRP is an ortholog of mammalian PrRP. These two types of PrRP are thought to be produced by whole genome duplication (Wang et al, 2012; Tachibana and Sakamoto, 2014).…”
Section: Orexigenic Neuropeptidesmentioning
confidence: 53%
See 2 more Smart Citations
“…Wang et al (2012) identified new chicken PrRP and showed that there are two types of PrRP encoded by separate genes. They also demonstrated that the chicken PrRP we previously identified (Tachibana et al, 2011; Tachibana and Sakamoto, 2014) is an ortholog of C-RFa, and newly identified chicken PrRP is an ortholog of mammalian PrRP. These two types of PrRP are thought to be produced by whole genome duplication (Wang et al, 2012; Tachibana and Sakamoto, 2014).…”
Section: Orexigenic Neuropeptidesmentioning
confidence: 53%
“…They also demonstrated that the chicken PrRP we previously identified (Tachibana et al, 2011; Tachibana and Sakamoto, 2014) is an ortholog of C-RFa, and newly identified chicken PrRP is an ortholog of mammalian PrRP. These two types of PrRP are thought to be produced by whole genome duplication (Wang et al, 2012; Tachibana and Sakamoto, 2014). Since newly identified chicken PrRP also increases food intake in neonatal chicks when administered centrally (Tachibana and Sakamoto, 2014), the role of PrRPs on feeding behavior is expected to have changed during the evolution of vertebrates.…”
Section: Orexigenic Neuropeptidesmentioning
confidence: 53%
See 1 more Smart Citation
“…A gene more lowly expressed in response to stress, Pro melanin concentrating hormone ( PMCH ) (logFC 3.8, FDR 2.532022e-05), can inhibit stress-induced ACTH release, stimulate anxiety and sexual behavior, and antagonize the inhibitory effect of alpha melanotropin on exploration behavior [3335]. C-RFamide protein , also known as prolactin releasing hormone 2 [36] was also more lowly expressed in response to stress and can play a role in the release of prolactin as well as several gonadotropes [37] (logFC 4.7, FDR 2.52e-05). No significantly enriched gene ontology terms were revealed for genes differentially expressed in the male hypothalamus in response to stress The full differential dataset for the stress response of the male hypothalamus is available at https://git.io/vD40k.…”
Section: Resultsmentioning
confidence: 99%
“…In line with this hypothesis, in the euryhaline fish mudskipper ( Periophthalmus modestus , Perciforme, gobidae), freshwater fish have lower food intake/growth rates than saltwater fish and higher brain and intestine PrRP mRNA expressions, suggesting that PrRP is involved in the regulation of feeding and energy homeostasis in this species (Sakamoto et al, 2002; Tachibana and Sakamoto, 2014). …”
Section: Hormones Involved In Food Intakementioning
confidence: 91%